2022
DOI: 10.53730/ijhs.v6ns3.9489
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of 5S management method for lean healthcare in clinical biochemistry laboratory of a government hospital in India

Abstract: Government healthcare organizations are facing big challenges as a result of increasing burden of diseases. Since the resources are limited, by restructuring the organizational infrastructure a better use of available resources is possible, which will improve the quality of services. The 5S approach is an effective tool of lean management principles which reduces waste through a better organized workplace, leading to improved quality service. The objectives of this study were to analyse the perceptions of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Singh et al [ 23 ] and Gupta et al [ 24 ] observed that implementing 5S contributed to fostering a positive mindset among staff regarding their duties and encouraged others to adopt the 5S methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al [ 23 ] and Gupta et al [ 24 ] observed that implementing 5S contributed to fostering a positive mindset among staff regarding their duties and encouraged others to adopt the 5S methodology.…”
Section: Discussionmentioning
confidence: 99%